Regulatory Clearance and Approval of Therapeutic Protocols of Transcranial Magnetic Stimulation for Psychiatric Disorders - Cotovio, Gonçalo (2023)
Funding Information: G.C. was funded by Fundação para a Ciência e Tecnologia (FCT; Portugal) through a PhD scholarship (SFRH/BD/130210/2017. G.C. and A.J.O.-M. were supported by grant PTDC/MED-NEU/31331/2017 from FCT. A.J.O.-M. was supported by grant PTDC/MEC-PSQ/30302/2017-IC&DT-LISBOA-01-0145-FEDER, funded by national funds from FCT and co-funded by FEDER, under the Partnership Agreement Lisboa 2020—Programa Operacional Regional de Lisboa, and by a Starting Grant from the European Research Council under the European Union’s Horizon 2020 Research and Innovation Programme (grant agreement no. 950357). A.J.O.-M. was also supported by the BOUNCE project (grant agreement no. 777167) and by the FAITH project (grant agreement no. 875358), both funded by the European Union’s Horizon 2020 Research and Innovation Programme. The content of this study is solely the responsibility of the authors and does not necessarily represent the official views of the Fundação para a Ciência e Tecnologia or the European Research Council. Publisher Copyright: © 2023 by the authors. Licensee MDPI, Basel, Switzerland.